Supporting groups’ emotion and motivation regulation during collaborative learning - Järvenoja, Hanna; Järvelä, Sanna; Malmberg, Jonna (Learning and instruction, 2020)
This study investigates when and how students activate co- and socially shared emotion and motivation regulation in collaborative learning and whether the S-REG mobile application tool can support this regulation. In a mathematics course, 44 higher education students worked with a collaborative assignment. The S-REG tool traced groups' emotional and motivational states in different sessions, and the occurrence of co-regulation and shared regulation of motivation and emotions were coded from video-recorded collaborative work (44 h). The groups activated more co-regulation than shared regulation of emotions and motivation, but the shared-regulation episodes were longer-lasting. The groups’ emotional and motivational states were associated with the occurrence of co-regulation in the beginning of the learning sessions. The results suggest that the S-REG tool balanced collaboration by prompting the groups to regulate emotions and motivation right in the beginning of the motivationally and emotionally challenging learning sessions. •Collaborative group members' regulation of motivation and emotions is infrequent.•Regulation in collaboration emerges throughout the learning process.•Socially shared regulation takes time when activated.•S-REG tool prompts groups' co-regulation when collaborative learning begins.